The Analysis of Cash Management to Cash Ratio At PT. Bima Indo Persada - Muhtar Muhtar; Puji Muniarty (Ilomata International Journal of Management, 2020)
The study was conducted at PT. Bima Indo Persada in Bima City. This study aims to determine how to manage the cash at PT. Bima Indo Persada. The type of study is descriptive. The data analysis techniques used are the one-sample test analysis by determining cash in and cash out (cash flow) in the financial statements of PT. Bima Indo Persada. Judging from the results of the data tabulation at PT. Bima Indo Persada, cash management is still unstable. Therefore, PT. Bima Indo Persada experienced an increase in cash in 2014 of 16.56%. In 2015, there was an increase in cash of 32.65% and 34.08% in 2016. In the previous three years, the cash management at PT Bima Indo Persada has been well by seeing this increase. The data collection techniques in this study use 4 methods, namely the method of observation, interviews, documentation, and study of literature. The authors hope that in the future PT. Bima Indo Persada will be better than the previous year in cash management. The problems at PT. Bima Indo Persada is the cash management that has not been balanced yet. The authors also hope that PT. Bima Indo Persada establishes good partners with the various financial institutions in Indonesia and in Bima City.